2013
DOI: 10.7748/en2013.12.21.8.36.e1237
|View full text |Cite
|
Sign up to set email alerts
|

Sudden death in emergency care: responding to bereaved relatives

Abstract: Many emergency nurses find it difficult to support relatives whose loved ones are being resuscitated or to witness relatives' distress after their family members have died. When such events occur, emergency practitioners have few opportunities to engage effectively with relatives and so they must get it right first time, every time. Consequently, they need to be able to give information sensitively, and express compassion and empathy, to bereaved relatives. This article discusses these issues and includes exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…In the United States, one of the most popular protocols is the so-called “ Six-Step Protocol” for the delivery of bad news (SPIKES: acronym for the words Setting, Perception, Invitation, Knowledge and Empathy). It is a protocol aimed primarily at doctors who provide information on unfavorable prognoses, but can also be used to inform the family of the death of a patient (Scott, 2013 ; Shomoossi et al, 2013 ; Williams-Reade et al, 2018 ). One study described the ABCDE notification strategies that propose accurate intervention plans for healthcare professionals who are required to make a death notification (Shomoossi et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the United States, one of the most popular protocols is the so-called “ Six-Step Protocol” for the delivery of bad news (SPIKES: acronym for the words Setting, Perception, Invitation, Knowledge and Empathy). It is a protocol aimed primarily at doctors who provide information on unfavorable prognoses, but can also be used to inform the family of the death of a patient (Scott, 2013 ; Shomoossi et al, 2013 ; Williams-Reade et al, 2018 ). One study described the ABCDE notification strategies that propose accurate intervention plans for healthcare professionals who are required to make a death notification (Shomoossi et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…The suffering of the suddenly bereaved and a self-perceived lack of experience and skills also had a bearing on the level of nursefamily engagement, with distancing potentially operating as a form of personal defence. Scott (2013) suggested that many emergency nurses find it difficult to witness the distress of bereaved relatives. This is confirmed in research exploring the lived experiences of nurses who have provided EoLC in A&E (Socorro et al, 2001) and within an intensive care unit (Holms et al, 2014;Stayt, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In collaboration with an experienced research liberian, we conducted a systematic literature search in the scientific research databases: Medline, PsychINFO, and Cinahl. We identified only sparse relevant literature about BID persons and their relatives (Chiang & Wang 1999, Kent & McDowell 2004, Scott 2013, Khursheed et al 2015, Naneix et al 2015, Mowll et al 2016, and none offered guidance of how to care for the adult BID relatives in an acute care setting.…”
Section: Accepted Articlementioning
confidence: 99%